Enucleation of Scrotal Epidermoid Cyst: Case Report - Halim Perdana Kusuma; Nugrohoaji Dharmawan (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Epidermoid cyst is one of the most common forms of blockage in the pilosebaceousgland. The surgical procedure for excision of the cyst aims to prevent recurrence, however, severalreports suggest that enucleation can be performed with certain considerations.Case:A 22 year old man who lives in Wonogiri, came to Dermatology and Venereology Outpatientclinicof Dr. Moewardi General Hospital Surakarta, with the chief complaint of a lump in the scrotum. Thelumps appeared since 3 years ago, the size of a pea seed and accompanied by itching. The resultsof the examination of the dermatological status of the scrotal region showed several nodules of theskin color, felt dense and rubbery without any signs of inflammation. Histopathology shows a basketwave type parakeratosis at the stratum corneum, while the epidermal layer shows cysts filled withkeratin and surrounded by squamous cells. Based on the results of the history, physical examinationand histopathology, the diagnosis of the patient was a scrotal epidermoid cyst, then we performed twoenucleation measures and found improvement.Conclusion: Epidermoid cyst is a form of benign epithelial cyst that can occur in the scrotal area. Themain treatment to prevent recurrences is surgery, where the enucleation technique can be performedwith several considerations such as small size of the cyst without signs of inflammation, preventingdystrophic calcification and capsule routine.